IMPLEMENTATION OF THE NATIONAL DEFENSE TRAINING IN LATVIAN SCHOOLS AS THE TOPICALITY OF NOWADAYS EDUCATION - Kreija - Gaikšte, Sandra; Katane, Irēna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Continuous changes in the global geopolitical space are highlighting our national interests in security matters, when thinking about the sustainability of our society and country. Both civic readiness to act in crisis situations and civic participation in strengthening national security are important. Therefore, following the introduction of a comprehensive National defense conception in Latvia, the acquisition of the subject of National defence training in secondary education programs will be compulsory from the academic year 2024/2025. The aim of the research was to substantiate the implementation of National defense traning in Latvian schools as a topicality of modern education. The new curriculum is included in the following areas of study: Health, Safety and Physical Activity and Social and Civic Learning. Nowadays,  in the framework of pilot project, the new curriculum in the field of national defense is already being experimentally tested in 69 educational institutions: secondary schools, gymnasiums, vocational schools, colleges. The results of the research allow to conclude that: 1) the concept of comprehensive national defense has four dimensions (military, informative, psychological and civic dimensions); 2) all these dimensions were respected in the development of the National Defense Training curriculum. The content of education in the field of national defense will serve as a means of patriotic upbringing, but the training process itself will have an upbringing function. The implementation of National defense training must also be based on an ecological approach in providing an appropriate educational environment, paying attention to the contexts of indoor and outdoor environments.